ASSISTANCE OF SSAI AS OUTDOOR ACTIVITIES IN MYOPIA PATIENTS - Didik Wahyudi; Mochammad Kholil; Ahmad Bunyamin (Jurnal Implementasi Pengabdian Masyarakat Kesehatan (JIPMK), 2021)
Background Visual acuity abnormalities are often found in children in the form of myopia, during the last 30 years the prevalence of myopia has increased rapidly. WHO estimates that the incidence of myopia is 23% worldwide and will increase to 50% by 2050. There is a protective effect of outdoor activities by decreasing the onset and progression of myopia, so the selected partners are SMPN 16 students who suffer from myopia.Partner problems Increasing the number of visual acuity experienced by students based on a survey conducted by the local health center. Changes in the environment due to the tool road project, the loss of the UKS room and several other spaces at SMPN 16 . The increasing use of gadgets by students, the behavior of students who do not like to be exposed to sunlight because they are afraid of the black and uncomfortable because of the heat. Preliminary surveys showed data on 63 students with myopia, 60% reported an increase in eyeglass size 0.25 D – 0.75 D.The initial mentoring method is coordination with SMP 16 and licensing and contacting related teachers. Screening and data collection for students with myopic refractive errors. Target recognition through socialization and lectures to increase knowledge about the importance of outdoor activities as a protective factor for myopia. The delivery of material lectures is carried out in 2 days with a duration of 120 minutes for each material, carried out on the sports field. Implementation of SSAI mentoring by students accompanied by sports teachers and service teamsThe solution given is healthy exercise for Indonesian children (SSAI) which has been evaluated by the Ministry of Youth and Sports as appropriate exercise material for junior high school students which is carried out on the second break 3 times a week for 1.5 months.Results The results of the screening obtained were refraction checks by the Refraction Optision staff obtained 223 students with myopia, students with myopia who were re-elected who were willing to take part in the service were 80 students divided into two groups.Conclusion This PKM activity was enthusiastically followed by students and ran smoothly without disturbing the learning activities. The school is very supportive of PKM activities because it can overcome the health problems experienced by students, namely myopia which in turn can support the smooth learning process of students.SSAI can be implemented continuously with implementation can be expanded in all schools. Keywords: mentoring, gymnastics, myopia, junior high school students.